Batch design of cementitious composites for the double-K fracture model - Ince, Ragip; Bildik, Abdullah Tevfik (Springer, 2023)
The concrete mixture design has been commonly conducted based on the compressive strength in concrete technology. Nevertheless, once a crack occurs in a structure, it can only be modeled realistically with the criteria of fracture mechanics. This investigation aims to accomplish some relationships between the fresh concrete properties such as the water/cement (w/c) ratio and the hardened concrete properties such as unstable fracture toughness and initiation fracture toughness. Therefore, twenty-two series of splitting square prismatic and wedge splitting (WS) specimens, with different w/c ratios and with two different maximum aggregate sizes (8 mm and 16 mm) were cast in this study. The two-parameter model (TPM) and the double-K model were used to simulate the results of the fracture toughness test. Subsequently, five mixtures with 20 mm crushed aggregate in the literature, which were previously analyzed according to the TPM for different w/c ratios, were modeled according to the double-K model in the current study. Consequently, two monograms combining the relationships between quantities of fresh concrete components and the aforementioned fracture toughness parameters were presented for concrete mixture design. Furthermore, a reliable approach based on the TPM was proposed for the WS test to determine unstable fracture toughness.
Keywords: Concrete; Double-K model; Fracture toughness; Mixture design; Two-parameter model